2007
DOI: 10.26439/persona2007.n010.934
|View full text |Cite
|
Sign up to set email alerts
|

Interrelación entre disociación, absorción y propensidad a la fantasía con experiencias alucinatorias en poblaciónes no psicóticas

Abstract: Interrelación entre disociación, absorción y propensidad a la fantasía con experiencias alucinatorias en poblaciónes no psicóticas

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 59 publications
0
3
0
3
Order By: Relevance
“…Sin embargo, los profesionales de enfermería se sienten incómodos al tratar con estas experiencias o cuestiones espirituales (14). De otro lado, en relación con el padecimiento de estas experiencias, no están relacionadas con trastornos mentales sino como un proceso mental normal (53-54) y presentan mayor grado de absorción (36)(37)(38)(39).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Sin embargo, los profesionales de enfermería se sienten incómodos al tratar con estas experiencias o cuestiones espirituales (14). De otro lado, en relación con el padecimiento de estas experiencias, no están relacionadas con trastornos mentales sino como un proceso mental normal (53-54) y presentan mayor grado de absorción (36)(37)(38)(39).…”
Section: Discussionunclassified
“…También se ha encontrado que personas con un elevado nivel de absorción tienen mayor probabilidad de padecer de estas experiencias, ya que, quizás, traten de tenerlas de manera intencionada o tengan más predisposición a explorar aspectos fenomenológicos que otros sujetos no puedan explorar (36)(37)(38)(39).…”
Section: Introductionunclassified
“…Though in clinical terms SCM theory has been the subject of controversy (for a review of different approaches see Gleaves, 1996; Manning & Manning, 2007; Lilienfeld et al., 1999), it may prove to be useful for explaining the high scores in nonclinical populations. As a continuous variable, dissociation (see Parra, 2007) may be high in specific groups of the general population, stemming partly from a conducive environment and have, in nonclinical environments with peculiar circumstances. Fine Art students work in an environment where creativity is fundamental, and where the type of methodology for achieving this knowledge favours divergent thought and requires considerable personal commitment.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have observed a positive relationship, though low, between dissociative experiences and absorption (Frischholz et al, 1991; Norton, Ross, & Novotny, 1990), and between absorption and the openness to experiences, the latter often being closely associated to creativity (Wild, Kuiken, & Schopflocher, 1995). Parra (2007) observed that the pronenes to fantasize was associated to psychological absorption, dissociative experiences, and hallucinatory experiences in nonclinical populations. Individuals have a great capacity for absorption, intense vivid visual imagery, intense sensorial and imaginary experiences, and a predisposition to hallucinatory experience, all under the umbrella of “normal” dissociation.…”
Section: The Dissociative Experiences Of Fine Arts Studentsmentioning
confidence: 97%
“…Pero no necesariamente significa que todas estas experiencias son puras fantasías alucinatorias, por ejemplo, las apariciones y otras experiencias similares están relacionadas con la absorción y la imaginación en estudiantes [37][38] , y creyentes en lo paranormal 39,71 , de modo que la experiencia de ver fantasmas puede estar relacionadas con procesos cognitivos que involucran fantasía y propensión a la esquizotipía cognitivo-perceptual y ambas están correlacionadas entre sí 36 .…”
Section: Funcionamiento Anómalo De Equipos O Intrumentalunclassified